Carpal tunnel syndrome in the mucopolysaccharidoses and related disorders. Issue 9 (September 1990) - Wraith, J E; Alani, S M
Abstract : Eighteen patients with various mucopolysaccharidoses or mucolipidosis III were studied electrophysiologically to determine the presence or absence of carpal tunnel syndrome. In 17 patients this was clearly demonstrated, the only exception being a boy with mucopolysaccharidosis II, age 6 months at testing. All patients had a remarkable lack of symptoms. Carpal tunnel syndrome is a very common complication of the mucopolysaccharidoses and mucolipidosis III and should be actively looked for in affected patients. Early diagnosis and treatment offer the best chance of a good response to surgery.